Force Control Benchmarking in the Gap Metric - Shime, Victor; Neto, José L. Montandon; Boaventura, Thiago (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
Force control technology has become increasingly prevalent, particularly in rehabilitation, precision, and legged robotics. These types of systems are expected to interact with environments with unknown dynamics, such as interaction forces, stiffness, damping, and inertia. In the current literature, there is a lack of performance indicators and, even more, stability indicators to evaluate the quality of force-based controllers. Stability indicators are important because they are directly related to safety and reliability in real applications. Moreover, most published works only test force controllers with a limited amount of loads (environments). This article proposes a stability indicator, based on the gap metric theory, to evaluate the dynamic behavior of force-control architectures of electric motors when coupled with a (possibly) infinite set of loads through a benchmark methodology. To this end, an experimental setup composed of motors and a torque sensor is built to validate the methodology. An approach to force control using the concept of transparency (residual forces) is also presented. The general results show acceptable applicability.